Evaluation of the quality of care of a haemodialysis public-private partnership programme for patients with end-stage renal disease. Issue 1 (December 2016) - Chen, Julie; Wan, Eric; Chan, Karina; Chan, Anca; Chan, Frank; Lam, Cindy
Abstract Background Haemodialysis (HD) is one of the life-saving options for patients with end stage renal disease but demand for this treatment exceeds capacity in publicly funded hospitals. One novel approach to addressing this problem is through a shared-care model whereby government hospitals partner with qualified private HD service providers to increase the accessibility of HD for needy patients. The aim of this study is to evaluate and enhance the quality of care (QOC) provided in such a shared-care programme in Hong Kong, the Haemodialysis Public-Private Partnership Programme (HD-PPP). Methods/Design This is a longitudinal study based on Action Learning and Audit Spiral methodologies to measure the achievement of pre-set target standards for the HD-PPP programme over three evaluation cycles. The QOC evaluation framework is comprised of structure, process and outcome criteria with target standards in each domain developed from review of the evidence and in close collaboration with the HD-PPP working group. During each evaluation cycle, coordinators of each study site complete a questionnaire to determine adherence with structural criteria of care. Process and clinical outcomes, such as adverse events and dialysis adequacy, are extracted from the patient records of consenting study participants while face-to-face interviews are conducted to ascertain patient-reported outcomes such as self-efficacy and health-related quality of life. Discussion The study relies on the successful implementation of partnership-based action research to develop an evidence-based and pragmatic framework for evaluation of quality of care in an iterative fashion, and to use it to identify possible areas of quality enhancements in a shared-care programme for HD patients. The approach we take in this study emphasizes partnership and engagement with the clinical and administrative programme team, a robust but flexible evaluation framework, direct observation and the potential to realize positive change. The experience will be useful to inform the process of coordinating research studies involving multiple stakeholders and results will help to guide service planning and policy decision making. Trial registration US Clinical Trial RegistryNCT02307903